Inquiry-Based Learning Through Contextual Scientific Activities on Students' Conceptual Understanding of Elements, Compounds, and Mixtures - Nabila Hanin Fitriani; Erman Erman; Kenneth Adu-Gyamfi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The majority of junior high school students find it difficult to understand the material on elements, compounds, and mixtures in science subjects. Some of them think that the material is very difficult to understand because it is not related to everyday life. This study examined the effect of inquiry-based learning (IBL) through contextual scientific activities on grade 8 students’ conceptual understanding of elements, compounds, and mixtures at SMP Negeri 4 Surabaya. By selecting 33 students purposively, a pre-experimental design of one group pretest–posttest was chosen as the study design. The IBL process was conducted in six meetings and involved three stages: contextual sharing sessions integrating material with real life, guided inquiry practicum using student scientific worksheet (SSW), and pre- and post-assessment via Kahoot!. Conceptual understanding was measured using the Normalized Gain score in the four cognitive dimensions of the revised Bloom's taxonomy (C1-C4). The 33 students were able to pass the low threshold and 18.2% of them reached the high category, resulting in an average N-Gain of 0.58 (moderate category). The average SSW achievement was 85.71% (very good), indicating that the engagement between practicum tasks and students was productive. The integration of IBL with activities based on contextually scientific activities at the junior high school level shows support for conceptual understanding of science about elements, compounds, and mixtures. Teachers teaching science concepts in junior high school are therefore encouraged to incorporate IBL through contextual scientific activities in teaching science